Advances in group processes. Vol. 35 - Thye, Shane R.; Lawler, Edward J. (Emerald Publishing Limited, 2018)
"Advances in Group Processes" publishes theoreticalanalyses, reviews, and theory-based empirical chapters on group phenomena. The series adopts a broad conception of "group processes." This includes work ongroups ranging from the very small to the very large, and on classic and contemporarytopics such as status, power, trust, justice, social influence, identity,decision-making, intergroup relations, and social networks.Volume 35 brings together papers related to a variety of topics in small groups andorganizational research. The volumeincludes papers that address theoretical and empirical issues relating toconsumer behavior, vocal accommodation, measuring aggression, social identitytheory, and criminal sentencing. Othercontributions examine reverse discrimination, perceptions of responsibility for the behaviors of others, and expectations and coordination in small groups. Overall, the volume includespapers that reflect a wide range of theoretical approaches from leadingscholars who work in group processes.
Prelims -- "Can a girl's best friend be born in a lab?": the role of ritual in production process conservatism -- Accelerometers as a methodological tool in group processes research -- Modeling small group status and power dynamics using vocal accommodation -- Identity theory paradigm integration: assessing the role of prominence and salience in the verification and self-esteem relationship -- Occupational status, impression formation, and criminal sanctioning: a vignette experiment -- Understanding white Americans' perceptions of "reverse" discrimination: an application of a new theory of status dissonance -- When do we feel responsible for other people's behavior and attitudes? -- Expectations and coordination in small groups -- Index.
Includes index.
Print version record
Keywords: Social groups; Social interaction; Psychology -- Social Psychology; Social, group or collective psychology